PRESERVASI BEKU SPERMATOZOA IKAN CUPANG (Betta splendens) STRAIN HALF-MOON DALAM MADU DAN NACL FISIOLOGIS - Rika Prihati Cahyaning Pertiwi; Isdy Sulistyo; Purnama Sukardi (Universitas Muhammadiyah Gresik, 2021)
A study entitled “Chilled Preservation of Spermatozoa Half-moon Strain Fighting Fish (Betta spendens) in Honey and Physiological NaCl”, was conducted to determine preserved spermatozoa motility and viability of Fighting Fish in honey and NaCl solutions, under chilling temperature (-250C). The study applied Completely Randomized Design (CRD) to examine three treatments, i.e aquadest, 0.09% NaCl and honey extenders, with quantuplicates. Data, being spermatozoa motility (%) and viability (time in second), were F-tested (ANOVA) and followed by LSD test (P<0.01). After storage of 7 days, the result showed that spermatozoa motility did not differ between treatments, however the viability of spermatozoa were significantly different (P<0.01). The highest viability was observed in sperm stored in extender Honey averaging 368.90±102.16 seconds, compared to the 0.09% NaCl extender (81.79±8.54 seconds), and aquadest (187.90±35.36 seconds). It was concluded that the Honey, NaCl 0.09% and aquadest as extenders could be used as preservation solution fighting fish spermatozoa. The best viability of spermatozoa was observed in honey extender.